Respuesta :
To find the gradient you differentiate
dy/dx = (5 - - 1) / (4 - - 3)
= 6 / 7
Then you put it into this formula
y - y1 = m (x - x1)
y1 being the y coordinate
x1 being the x coordinate
m being the gradient (or slope)
y - 5 = 6/7 (x - 4)
y - 5 = 6/7x - 24/7
y = 6/7x + 11/7
dy/dx = (5 - - 1) / (4 - - 3)
= 6 / 7
Then you put it into this formula
y - y1 = m (x - x1)
y1 being the y coordinate
x1 being the x coordinate
m being the gradient (or slope)
y - 5 = 6/7 (x - 4)
y - 5 = 6/7x - 24/7
y = 6/7x + 11/7